2021
DOI: 10.25165/j.ijabe.20211401.5621
|View full text |Cite
|
Sign up to set email alerts
|

Field test and evaluation on crop dividers of sugarcane chopper harvester

Abstract: In South China, the tropical weather and climate result in severe sugarcane lodging problems which greatly hinders sugarcane mechanical harvesting. The main function of the crop divider is to lift lodged canes and facilitate base-cut cane feeding. In this study, a series of field tests were conducted on crop dividers of Liugong 4GQ-180 sugarcane chopper harvester. The tests were designed to identify the relationships of the performance index (maximum lifting height of sugarcane) and the main influencing factor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…Bai et al investigate the biological effects of a 4 kV/m electrostatic field on barley seeds and 4.5 kV/m sugar beets for 10 minutes. Their results showed that electrostatic fields of a certain intensity can increase the amount of free radicals in seeds [9]. Rotcharoen et al studied the effect of electric field on rice growth and found that electric field strengths of 193 kV/m and 4 kV/m had a significant effect on the growth rate and height of rice plants [10].…”
Section: Introductionmentioning
confidence: 99%
“…Bai et al investigate the biological effects of a 4 kV/m electrostatic field on barley seeds and 4.5 kV/m sugar beets for 10 minutes. Their results showed that electrostatic fields of a certain intensity can increase the amount of free radicals in seeds [9]. Rotcharoen et al studied the effect of electric field on rice growth and found that electric field strengths of 193 kV/m and 4 kV/m had a significant effect on the growth rate and height of rice plants [10].…”
Section: Introductionmentioning
confidence: 99%
“…A triangle tracked chassis for a sugarcane harvester was designed by Bai Yuanqiang. The adaptability of a triangle track and flat track combination to slope ground was better than that of a traditional track sugarcane harvester [12]. A four triangular tracked camellia fruit picking machine with good adaptability to southern gentle slope land was developed by Cai Gangchu [13].…”
Section: Introductionmentioning
confidence: 99%
“…For the finger chain type, Mou et al carried out simulation analysis and bench test research on the problems of missing support and lift lodging angle parameters [19]. At present, sugarcane harvesters on the market mostly still employ the installation of spiral crop dividers, and interested scholars have carried out a series of studies into this [20]. In [18,20], the effects of different lodging angles, forward velocity (FV), scrolls speed and the ground clearance of the crop divider toes on lifting performance were investigated in a field experiment.…”
Section: Introductionmentioning
confidence: 99%
“…At present, sugarcane harvesters on the market mostly still employ the installation of spiral crop dividers, and interested scholars have carried out a series of studies into this [20]. In [18,20], the effects of different lodging angles, forward velocity (FV), scrolls speed and the ground clearance of the crop divider toes on lifting performance were investigated in a field experiment. It was concluded that it is necessary to improve the operational performance of the crop divider for different inversions of sugarcane.…”
Section: Introductionmentioning
confidence: 99%